2022
DOI: 10.1111/jgh.15866
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of a novel device delivery system in the diagnosis of bile duct lesions: A single‐center experience

Abstract: Background and Aim Pathological evaluation is essential for the diagnosis of biliary tract diseases. However, existing evaluation methods have various challenges in terms of operability and diagnostic performance. The present study aimed to evaluate the feasibility, utility, and safety of a novel device delivery system for bile duct biopsy. Methods This study was conducted as a retrospective, descriptive analysis at a single center. Overall, 25 examinations in 14 consecutive patients who underwent transpapilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…A retrospective single-center study evaluated TBFBs using this novel delivery device in 14 patients and revealed high diagnostic yields of 90% and 92.3% in sensitivity and accuracy, respectively, making it a promising method for TBFB [12]. However, there have been no comparative studies of TBFB using this novel sheath device and conventional TBFB.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A retrospective single-center study evaluated TBFBs using this novel delivery device in 14 patients and revealed high diagnostic yields of 90% and 92.3% in sensitivity and accuracy, respectively, making it a promising method for TBFB [12]. However, there have been no comparative studies of TBFB using this novel sheath device and conventional TBFB.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Recently, we developed a novel delivery device composed of an inner catheter with a tapered tip and an outer sheath with no caliber difference. With this device, various devices up to 6 Fr can be delivered into the bile duct through the outer sheath, which has an inner diameter of 6.5 Fr 3 4 . In this case, not only did the tapered shape and moderate stiffness of this novel device aid its passage through the U-SEMS meshes, but the outer sheath also served as a conduit for easy placement of an ENBD tube ( Fig.…”
Section: Endoscopy E-videosmentioning
confidence: 99%
“…In 1 patient with gallbladder neck wall thickness, the gallbladder anatomy made it difficult to accurately assess whether a biopsy could be performed from the target site. The median number of biopsies was 5.5 (3)(4)(5)(6)(7)(8). Appropriate evaluable specimens were obtained in all 10 patients in which biopsies were taken from the gallbladder.…”
Section: Accepted Manuscriptmentioning
confidence: 99%